2006
DOI: 10.1242/jeb.02490
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional recovery of the goldfish (Carassius auratus) ear following noise exposure

Abstract: Many vertebrates, including fishes and marine mammals, rely on acoustic signals for communication. In aquatic environments, where sound propagates five times faster than in air, acoustic signals are particularly important for communication over long distances or in low-light environments. Research on a variety of fishes, however, demonstrates sensitive hearing capabilities even in nonvocalizing fishes, leading to the hypothesis that hearing in fishes evolved for analysis of the complete auditory scene, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 77 publications
2
128
1
Order By: Relevance
“…44a). In a subsequent study Smith et al (2006) exposed goldfish to white noise of 170 dB for 48 h and found a small 4 dB TTS after 7 days of recovery (Fig. 44b).…”
Section: Exposure To White Noisementioning
confidence: 81%
“…44a). In a subsequent study Smith et al (2006) exposed goldfish to white noise of 170 dB for 48 h and found a small 4 dB TTS after 7 days of recovery (Fig. 44b).…”
Section: Exposure To White Noisementioning
confidence: 81%
“…In contrast to mammals, many fish species have the ability to regenerate their inner ear and lateral line hair cells after damage (Kaus, 1987;Lombarte et al, 1993;Song et al, 1995;Scholik and Yan, 2001;Faucher et al, 2006;Smith et al, 2006). Given their capacity for regeneration, fish inner ear hair cells are nowadays a suitable model for investigations on hair cell regeneration and hearing function in animals.…”
Section: Introductionmentioning
confidence: 99%
“…These temporary threshold shifts were first documented in goldfish (Popper & Clarke 1976), and have been confirmed more recently in several other species of fish (Scholik & Yan 2001, Amoser & Ladich 2003, Smith et al 2004, 2006. This recovery in hearing is most likely due to the proliferation of new hair cells (Popper & Hoxter 1984, Lombarte & Popper 1994 or the regeneration of damaged ones (Lombarte et al 1993, Smith et al 2006, Schuck & Smith 2009), al though there may be other mechanisms involved for temporary shifts in hearing. As we do not know whether snapper hearing would recover post-noise exposure, recovery experiments are needed to elucidate this.…”
Section: Discussionmentioning
confidence: 64%